Bending of plates with transverse shear deformation: The Robin problem. Issue 2 (29th March 2019) - Constanda, Christian; Doty, Dale
Abstract : The Robin problem in a finite domain for the system of equations describing the bending of elastic plates with transverse shear deformation is solved by means of a generalized Fourier series method based on the structure of the governing system. The numerical illustration of the results, obtained by three different computational methods, is also provided.